2003
DOI: 10.2337/diabetes.52.10.2630
|View full text |Cite
|
Sign up to set email alerts
|

Kir6.2 Polymorphisms Sensitize β-Cell ATP-Sensitive Potassium Channels to Activation by Acyl CoAs

Abstract: The commonly occurring E23K and I337V Kir6.2 polymorphisms in the ATP-sensitive potassium (K ATP ) channel are more frequent in Caucasian type 2 diabetic populations. However, the underlying cellular mechanisms contributing to the pathogenesis of type 2 diabetes remain uncharacterized. Chronic elevation of plasma free fatty acids observed in obese and type 2 diabetic subjects leads to cytosolic accumulation of long-chain acyl CoAs (LC-CoAs) in pancreatic ␤-cells. We postulated that the documented stimulatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 34 publications
9
76
0
3
Order By: Relevance
“…However, the mechanism by which this is achieved is controversial. A twofold reduction in the ATP sensitivity of Kir6.2/SUR1 channels (64) and Kir6.2/SUR2A channels (65) has been reported when E is mutated to K, yet a third study found little effect on ATP block (66). Minor variations in experimental protocol or DNA species (human versus mouse) might account for this difference.…”
Section: Discussionmentioning
confidence: 89%
“…However, the mechanism by which this is achieved is controversial. A twofold reduction in the ATP sensitivity of Kir6.2/SUR1 channels (64) and Kir6.2/SUR2A channels (65) has been reported when E is mutated to K, yet a third study found little effect on ATP block (66). Minor variations in experimental protocol or DNA species (human versus mouse) might account for this difference.…”
Section: Discussionmentioning
confidence: 89%
“…It is also pertinent that a common polymorphism (E23K) in KCNJ11 is associated with an increased risk of type 2 diabetes in humans (18). The functional effects of this polymorphism remain controversial (19,20), but our finding that neonatal diabetes (a far more dramatic phenotype) is produced by only a subtle shift in the ATP concentration-inhibition curve suggests that the effects of a Kir6.2 gene variant predisposing to diabetes in later life may be hard to discern experimentally, particularly in the heterozygous state.…”
Section: Resultsmentioning
confidence: 99%
“…Functional studies indicate that this polymorphism significantly influences channel gating properties [48][49][50]. In vivo, human carriers of the lysine risk allele demonstrate impaired insulin secretion [44,46].…”
Section: Kcnj11: From Mendelian To Common Disease and Backmentioning
confidence: 99%